Securing university wrestlers' technical and tactical progress based on competitive performance quality rating data - Barkov, A. Y. (Theory and Practice of Physical Culture, 2017)
Abstract: The study gives an overview of National Research Moscow State University of Civil Engineering (NRMSUCE) picked freestyle wrestlers` technical and tactical progress (TTP) rating methodology based on the competitive performance rating data and analyses of the NRMSUCE athletes versus those of the top-ranking competitors in the Moscow Student`s Sport Games (MSSG) for the period of 2013-15. The study data and analyses gave the means to offer the following practical recommendations to the university wrestlers: - Focus on the holds and inside-distance wins, i.e. cut down the average fight time; - Expand the range of attacking actions to step up the average individual score to 30-35 points; - Excel the quality of holds and completed techniques to the best possible level.